Target vessel–specific efficacy and short-term outcomes of rotational atherectomy in the treatment of chronic total occlusion - Zhang, Bin; Sun, Yurong; Bai, Hangrui; Zhang, Xiaojiao; Wang, Xinran; Luan, Bo (Frontiers in Cardiovascular Medicine, 2025)
AimTo compare the procedural features, treatment efficacy, and short-term outcomes of RA for CTO in different target vessels—LAD, LCX, and RCA—and to assess the anatomical compatibility and clinical benefit of RA.MethodsThis retrospective study included 119 patients with single-vessel CTO who underwent RA-assisted PCI from January 2019 to December 2024. Patients were divided into LAD (n = 55), LCX (n = 14), and RCA (n = 50) groups. Clinical characteristics, procedural details, and 6-month MACCEs were compared. Kaplan–Meier and Cox regression analyses were used to assess outcomes and predictors.ResultsRCA-CTO patients were older and had more triple-vessel disease, but showed the lowest MACCEs rate at 6 months (10.0%) compared with LAD (23.6%) and LCX (28.6%) (P = 0.116). The difference between RCA and non-RCA groups was statistically significant (P = 0.042), the incidence was 10.0% in the RCA group and 24.6% in the non-RCA group (post hoc). Burr size and intravascular imaging use were similar across groups, though the RCA group had longer stents and used more contrast. Cox analysis showed potential trends between MACCEs and factors like imaging use, HDL, and triple-vessel disease, but none reached significance.ConclusionRA-assisted PCI is safe and feasible for heavily calcified CTO lesions. Observed outcomes showed some variation by target vessel, with RCA-CTO appearing to have relatively better short-term results. Intravascular imaging may be helpful for guidance, but in this cohort it was not associated with a statistically significant reduction in 6-month MACCEs.